CONFLICT TO CLARITY: MEDIATION IN RESOLVING COPYRIGHT DISPUTES OVER ELECTRONIC BOOKS - Waruwu, Khamozaro; Dare, Foluke M (Jurnal Pembaharuan Hukum, 2024)
Mediation as one of the efforts to resolve e-book copyright disputes has become a trend in society to utilize dispute resolution with various advantages, including economic factors, legal culture factors, the breadth of the scope of problems that can be discussed, and coaching factors. The purpose of this paper is to discuss mediation as one of the alternatives to resolving e-book copyright disputes. Intellectual Property Rights are referred to as property rights, and the results of this work can be in the form of intangible objects that come from the work of the brain and the work of rational reason that gives birth to intellectual property rights. Mediation is one type of dispute resolution that can be chosen in resolving problems in the field of IPR, especially regarding e-book piracy disputes that are currently rampant. This study uses a normative legal research method with two types of approaches, namely the statutory research approach and the case research approach. Mediation is the most effective alternative dispute resolution and is needed for copyright disputes because it is regulated in the Copyright Law. In addition, the form of dispute resolution through mediation also has other advantages in that it can be resolved peacefully.